Toxic Parent in A Thousand Perfect Notes by C.G. Drew - Alya, Mazaya Shauqina (English Literature Study Program, 2023)
This study examines the portrayal of a toxic parent in C.G. Drews's novel, A Thousand Perfect Notes, explicitly focusing on the mother's role in forcing her child to become a pianist. The research addresses two mainobjectives: the first is to describe the forms of toxic parenting exhibited by the mother in the novel, and the second is to explore the effects of toxic parenting on the child's character in A Thousand Perfect Notes. Toachieve this, the researcher applied Dr. Susan Forward's theory of toxic parents from 2002, utilizing a psychological approach for analysis. In addition, the study utilized a psychology-focused literary criticismapproach, focusing on the character's parenting style. The findings revealed several forms of toxic parenting depicted in the book, including insufficient parenting, controlling behavior, verbal abuse, and physicalabuse. The main character, in particular, experienced the impacts of these toxic parent characteristics. The study's analysis shed light on the effects of a toxic parent on a child, as portrayed in C.G. Drews's A ThousandPerfect Notes.